IMPACTS OF THE EL NIÑO AND LA NIÑA EXTREME CLIMATE ON SOCIO-ECONOMIC AND POLITICS IN INDONESIA - Herlina Amrianah (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal